Strategi Pengembangan Asuransi Tanaman Kelapa Sawit Dengan Pendekatan Model Bisnis Kanvas (Studi Kasus Di PT Asuransi Tri Pakarta) - Sunarto; Daryanto, Arief; Maulana, Agus (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Indonesia is the largest country producing palm oil. The existence of climate change in the form of El Nino has had an impact on the sustainability of oil palm plantations, with the fire of land and oil palm plantations. The purpose of this study is to design a prototype of future business models that will be used to develop palm oil insurance. The analytical method used is a business model canvas (BMC) approach equipped and SWOT. Data used in the form of primary data and secondary data. Data collection is done through observation, interviews, questionnaires and literature studies. The sampling technique is by non-probability sampling-purposive sampling with the hope that the selected sample has the knowledge, expertise and competence in the field studied in this study. Based on the results of the research, it shows that the highest strength lies in the elements of Key Partners and Channels with values of 4.1 and 3.7. Furthermore, the highest weaknesses are indicated by Key Activities and Key Resources elements with values of 3.10 and 3.00. Both have relatively low weaknesses compared to the weaknesses of other elements. The highest opportunity lies in the Customer Segment element with a value of 4.2 and Customer Relationship with a value of 3.97. Threats in all segments are classified as low with values between 3 and 3.4. High weakness in the Revenue Stream and Cost Structure elements. Company need to improve elements: customer relationship, value preposition, key activities, key partners, key resources, and channels. Keywords: BMC, insurance for palm oil plantation, strategy, business model, SWOT